PENGARUH IMPULSE BUYING DAN PROMOSI TERHADAP MINAT BELI ULANG AIR MINUM MASAK DI DEPOT AZAY - Nurhayati, Agustin; Ritonga, Zuriani; Safri, Hayanuddin; Sufitrayati, Sufitrayati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
The purpose of this research is to analyze the Azay Boiling Water Depot in Juang Bireuen City to find out how impulsive purchases and promotions influence customers' interest in purchasing boiled water. The research here is purely descriptive. Although 98 customers made up the sample, little is known about the population as a whole. Observation, interviews, questionnaires, and documentation studies were used to gather data. Smart PLS (Partial Least Square) 3.0 was used for the analysis of this research. The results indicated that both impulse buying and promotion had a positive and significant impact on consumers' buying interest. This is supported by the fact that the T-Statistics value was greater than 1.96 and the P-Value was less than 0.50, indicating that the hypothesis test in this study was accepted or valid. An R-Square value of 0.901 for the purchase intent variable is readily apparent. This indicates that a 90.1% relationship exists between the two variables, with impulsive purchases and promotions having the greatest impact on consumer interest.